Delayed polishing technique on glass-ionomer restorations - Masao Irie; Kazuomi Suzuki; David C. Watts (Elsevier, 2009)
This in vitro study evaluated the effect of polishing after 1-day storage in water on the gap-formation around a Class V and Class I restorations, using a resin-modified glass-ionomer and a conventional glass-ionomer materials. The study also examined the gap-formation in another two different cervical restorations, a cervical cavity: incisally bordered by enamel and cervically by dentin and a root surface cavity of these restorative materials, which may be effects of this polishing procedure. This study evaluated the effects of delayed versus immediate polishing to permit maturation on: (1) interfacial gap-formation around resin-modified (RMGIC) and conventional (CGIC) in three types of cervical restorations, (2) interfacial gap-formation around highly viscous conventional glass-ionomer cement (HCGIC) in Class I restorations. After polishing procedure, either: (i) immediately (3 or 6 min) after setting or (ii) after 24 h storage, the maximum the restored teeth were sectioned in a mesio-distal direction through the center of the restorations. The presence or absence of interfacial-gaps was measured at 14 points (each 0.5-mm apart) along the cavity restoration interface. For various restorative cases, significant differences (p < 0.05) in gap-width or gap-incidence, were observed between polishing (i) immediately and (ii) after 1-day storage.